Study on the nonlinear performance degradation of reinforced concrete beam under chloride ion corrosion. (June 2021) - Wen, Qing-qing; Chen, Meng-cheng
Highlights: An effective CA model provides simulation of diffusion process of chloride ions in concrete. An effective MATLAB program provides the nonlinear analysis of corroded RC beams. The time-variant nonlinear performance degradation process of corroded RC beam. The life assessment of RC structures in corrosive environment. Abstract: The chloride-induced corrosion deteriorates the performance of reinforced concrete (RC) structures. This paper proposes a novel method for the nonlinear analysis of RC structures under chloride ion corrosion based on the cellular automata (CA) method and the fiber model of FEM. The CA model is established to simulate the chloride diffusion in cross-section of RC continuous T-beam, then the time-varying chloride ions concentration in cross-section are evolved. The damage indices corresponding to the corrosion of steel bar and deterioration of concrete have been defined and their variations with time are discussed. Following that, the CA model is coupled with the fiber model of FEM to compile an matlab program to analyze the performance of corroded RC continuous T-beam. Thus the deflection-time curve, the load–deflection curve, the strain distribution of cross-section, the bending moment–curvature curve and the time evolution of bending moment for the T-beam are obtained to discuss the time-variant nonlinear performance degradation process of corroded RC beam. It can be concluded that the proposed CA model can effectively and accurately simulate the diffusion process of chloride ions in concrete. Besides, the damage model introduced in this paper can quantifies the relationship between the damage caused by chloride ions and corrosion time. Furthermore, the matlab program established in the present study can be effectively applied to the nonlinear analysis of corroded RC beams. Considering the co-action of geometric and material non-linearity and corrosion, the calculation results can more accurately describe the actual stress process of the RC structure. Finally, the proposed method can be used as a effective theoretical tool for the life assessment of RC structures in corrosive environment.